Single-cell transcriptomics identifies FOSL1-regulated IGFBP3+ melanoma subtype as a neuro-immunoregulatory signaling hub facilitating tumor progression - Ge, Wenjia; Zhang, Ziwei; Chen, Wenjie; Zhao, Zhijie; Cai, Huabao; Ding, Yantao; Xu, Jin (Frontiers in Immunology, 2025)
BackgroundThe most aggressive type of skin cancer, melanoma, has a high prevalence of metastases and a poor prognosis. Despite advancements in treatment, drug resistance and tumor microenvironment heterogeneity, especially involving neuro-immune interactions, continue to exist. The goal of this study is to uncover the cellular heterogeneity of melanoma in order to pinpoint molecular targets and tumor-promoting subtypes.MethodsMelanoma single-cell RNA sequencing data came from GEO. Twelve cell types were discovered after Harmony batch effect adjustment and Seurat quality control; melanoma cells were subtyped. Functional expression of differential genes was examined using gene ontology and gene set enrichment. Cytotrace measured subtype differentiation potency. PySCENIC revealed transcription factor regulatory networks, and CellChat predicted intercellular communication between malignant cell subtypes and other cell types. Functional experiments with A375 and MEWo cell lines—lentiviral shRNA knockdown, CCK-8 proliferation, wound healing, transwell migration, and flow cytometry apoptotic assays—confirmed the analysis.ResultsSingle-cell RNA sequencing was utilized to analyze melanoma cell subtypes and their interactions in the tumor microenvironment. C2 IGFBP3+, which had the lowest CytoTRACE2 score and was enriched in late tumor stages, affected melanoma development. This subtype expressed prominent immunomodulatory pathways. The C2 subtype mediate signaling to fibroblasts/pericytes via the PROS pathway and myeloid/plasmacytoid dendritic cells via the MHC-II pathway. The C2 subtype was strongly linked with FOSL1 expression, which may affect gene transcription and illness progression. FOSL1 knockdown significantly increased apoptosis and decreased melanoma cell motility and proliferation in vitro.ConclusionWe identified immunoregulatory C2 IGFBP3+ melanoma cell subtypes in our investigation, and FOSL1 was a crucial transcription factor that aided in cell migration, proliferation, and survival. Because the C2 subtype involves the MHC-II and PROS signaling pathways, which have been shown to have roles in neuroimmunology, neuroinflammation, and pain regulation, it may serve as a hub for neuro-immune interactions in the tumor microenvironment. Precision treatments for melanoma may be advanced by focusing on the FOSL1 or C2 subtype pathways, which may assist in overcoming immunotherapy resistance.